Optimization of Google Classroom as a Digitalization Alternative to Improve English Learning Outcomes - Sugiarto, Adi Tia; Suseno, Muchlas (Scaffolding: Jurnal Pendidikan Islam dan Multikulturalisme, 2024)
This study seeks to provide benefits and information about the optimization of using Google Classroom as an alternative to digitization in English distance learning as a solution to complete the online learning process. The methodology of quantitative descriptive analysis is the research approach employed. This research was conducted in one of the elementary schools in West Java with a total of 823 students, and by using a purposive sampling technique, 122 sixth-grade students in the 2023/2024 school year were selected. The sample of this study was students from the upper-grade level, where each subject taken from the population is chosen intentionally based on the class group selection. The data were collected by using observation, interview, and documentation. The data were analyzed and interpreted through qualitative. Results showed that optimizing the use of Google Classroom can be used to develop online learning with high results, 73.57%. Based on these data, it can be concluded that Google Classroom-based e-learning media can improve English results for elementary school students.